SOCIOMETRIC RESEARCH IN THE SERVICE OF APPOINTING MANAGERS IN THE AGRICULTURAL PHARMACIES - Ivica Dragomir Nikolic; Jelena Vemić Djurković; Ivana Ivana Marinović Matović (Ekonomika Poljoprivrede (1979), 2020)
The purpose of this paper is to prove possibility of the application of the sociometric method in human resources management with the aim of appointing managers in one organization. Based on the some results, published in the scientific papers, authors established general and particular hypothesis about applying sociometry as a research method in human resources management. The concrete research of the applications of sociometry for appointing managers was conducted in one company in Serbia. Sociometric research shows real relations in a social group, as well as the projection of the position of individuals, mutual attraction and rejection within the group. Presented research is one of the "pioneering" attempts of broader application of the sociometric method in human resources management with the aim of appointing managers in one organization, especially in Serbia.